Pengenalan Structural Equation Modeling dengan Lisrel dalam Olah Data Kuantitatif - Sugeng; Chelda Yuliana; Muhammad Yamin; Abd. Wahab Syahrani; Hasbi Sjamsir (TAAWUN, 2023)
Processing data as a way to generate meaningful information to support accurate decision-making. Quantitative data processing training was conducted at SDN 004 Samarinda Ilir and SMA IT Granada Samarinda, attended by 13 S3 Education Management (MP) students, 8 S2 MP students, and elementary school teachers. Training materials include theory and continued practice of SEM analysis with LISREL. The results of the training showed that some participants successfully practised PRELIS analysis and continued LISREL investigation successfully, but some were still at the level of familiarity with the application. Based on feedback, participants gave "Excellent" and "Good" responses for the training material aspect 93,181%, an average of 95,454% for the resource person aspect, and 82,954% of participants stated that the provision of room and consumption facilities was feasible. Participants admitted that this SEM training material supports completing the S3 and S2 MP final projects. For further training, it is necessary to implement other applications, even with qualitative data, to provide a more varied data processing experience.